2018
DOI: 10.1155/2018/4567206
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon Association of Two Anatomical Variants of Cerebral Circulation: A Fetal-Type Posterior Cerebral Artery and Inferred Artery of Percheron, Complicated with Paramedian Thalamomesencephalic Stroke—Case Presentation and Literature Review

Abstract: Background The unilateral fetal variant of the posterior cerebral artery (FPCA) is characterized by the congenital absence of the P1 arterial segment. The artery of Percheron (AOP) is an uncommon vascular variant, in which a single dominant thalamoperforating arterial trunk arises from one P1 segment, bifurcates, and provides bilateral supply to the paramedian thalami and rostral midbrain. Case Presentation This is a retrospective case study of a 37-year-old man with multiple lifestyle risk factors (chronic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Thirdly, when severe stenosis or occlusion of internal carotid artery causes changes in hemodynamics, cFTP cannot quickly and effectively establish the compensation of lateral branches of the posterior circulation through the posterior communicating artery of the anterior circulation, and the compensation of lateral branches of pia meningeal anastomosis between the posterior cerebral artery, middle cerebral artery and anterior cerebral artery. Even in the presence of pFTP, it is possible that the ipsilateral internal carotid artery-posterior communication artery-posterior cerebral artery P1 segmentbasilar artery collateral circulation of pFTP is established to compensate for severe basilar artery stenosis or occlusion, further aggravating anterior circulation ischemia, thus increasing the risk and severity of anterior circulation cerebral infarction in patients [1,[11][12][13][14]. In addition, since FTP completely belongs to the internal carotid artery system, when the internal carotid artery system is completely occluded, hypoperfusion or embolus fall off, simultaneous infarction of the anterior and posterior circulation contrary to the normal situation may occur (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, when severe stenosis or occlusion of internal carotid artery causes changes in hemodynamics, cFTP cannot quickly and effectively establish the compensation of lateral branches of the posterior circulation through the posterior communicating artery of the anterior circulation, and the compensation of lateral branches of pia meningeal anastomosis between the posterior cerebral artery, middle cerebral artery and anterior cerebral artery. Even in the presence of pFTP, it is possible that the ipsilateral internal carotid artery-posterior communication artery-posterior cerebral artery P1 segmentbasilar artery collateral circulation of pFTP is established to compensate for severe basilar artery stenosis or occlusion, further aggravating anterior circulation ischemia, thus increasing the risk and severity of anterior circulation cerebral infarction in patients [1,[11][12][13][14]. In addition, since FTP completely belongs to the internal carotid artery system, when the internal carotid artery system is completely occluded, hypoperfusion or embolus fall off, simultaneous infarction of the anterior and posterior circulation contrary to the normal situation may occur (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…He mentioned thar 6% of the specimens had an incomplete circle owing to the non-existence of the P1 segment of the PCA. The complete agenesis of P1 segment may be encountered bilaterally in 2% to 4% of cases [ 14 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Fetal posterior cerebral artery (FPCA) represents an anatomic variant of PCA, deriving directly from the ICA, without having a link with the BA [ 14 , 15 , 16 ]. The embryonic origin of the PCA was detected by angiographic studies in 11% to 46% of the general population, most commonly being found unilaterally (4–26%), while bilaterally was found in only 2–4% of cases [ 2 , 11 , 12 , 13 , 14 , 15 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main side effects are: CBF decrease, predisposition for CSVD-ld, WMHs, endothelial dysfunction with predisposition for thromboembolism, demyelination processes and axonopathies, increased insulin resistance, diabetes, metabolic syndrome, heart attack, stroke (Hassan et al, 2004) (Figure 10). The CBF imbalance between the anterior and posterior poles, favored by the hypoperfusion of the posterior pole after acute psychotic episodes, where the hyperperfusion is located in the frontal pole, may be associated with anomalies of the circle of Willis or of artery of Percheron irrigating the thalamus (Anghelescu, 2018). In the case of hypoperfusion in arterial supply of choroid plexus, the excessive release of extracellular calcium determines calcification of choroid plexus and pineal gland.…”
Section: Homocysteinementioning
confidence: 99%